2022
DOI: 10.47992/ijmts.2581.6012.0213
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Literature Review on Training Higher Education Students for Soft Skills

Abstract: Purpose: The research entails drawing up new ideas and laying down them into action while availing former work as a foundation. The impetus of the literature review in this paper is to acquaint and learn about the review topic to amalgamate existing ideas with the new ones. Methodology: Multiple secondary sources, such as journals, conference proceedings, book chapters, and other web resources, were utilised to compile the literature for this study. All of the literature has been reviewed in-depth and is encap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…According to Pai and Mayya (2022) research, it is confirmed that Malaysian graduates highly prioritize soft talents, such as proficient English language abilities, computer technology, etc. According to the World Economic Forum (2020), there is an increasing recognition and value placed on soft talents.…”
Section: Introductionmentioning
confidence: 99%
“…According to Pai and Mayya (2022) research, it is confirmed that Malaysian graduates highly prioritize soft talents, such as proficient English language abilities, computer technology, etc. According to the World Economic Forum (2020), there is an increasing recognition and value placed on soft talents.…”
Section: Introductionmentioning
confidence: 99%
“…However, the state of higher education in the 21 st century has become a matter of concern to many, especially regarding the preparation of students for the workforce. Pia and Mayya [2] have asserted that higher education institutions (HEIs) must "rethink their coaching and study methods to generate job-ready graduates". This implies that traditional teaching and learning methods in higher education may not have effectively prepared graduates for the workplace.…”
Section: Introductionmentioning
confidence: 99%